Insight into Tar Formation Mechanism during Catalytic Pyrolysis of Biomass over Waste Aluminum Dross - Liu, Peng; Liu, Li; Zhou, Zhengzhong; Yuan, Haoran; Zheng, Tao; Wu, Qigang; Taoli, Huhe (Applied sciences, 2021)
Tar is one of major products from biomass pyrolysis. Its formation mechanism in a catalytic pyrolysis system comprising pine sawdust and waste aluminum dross (AD) is investigated with the aid of analytical methods including thermogravimetric analysis (TG), Nuclear Magnetic Resonance (NMR), electron paramagnetic resonance (EPR), and gas chromatography coupling with mass spectrometry (GC-MS). The results show that AD plays a vital role in cleavage of C-O bonds to enhance selective formation of furans, ketones, and phenols. The catalytic pyrolysis is initiated by active C-O-M intermediate formation that accelerates C-O bond cleavage and generates great amounts of free radicals to 1020 spins/g at 300–500 °C. Compared with pure pine pyrolysis, the percentage of glucosidic bonds from cellulose decreases from 14.00% to 9.66% at 500 °C; the etherified guaiacyl is more actively ruptured and disappears at 700 °C. Furans and ketones increase from 17.45% to 22.23% and 6.71% to 10.80% at 500 °C, respectively. Phenols increase from 66.75% to 71.57%. The preferential production of higher value-added products via catalytic pyrolysis between biomass and industrial wastes may bring new insight to the simultaneous valorization of agricultural, municipal, and industrial waste.